2022
DOI: 10.3389/fphys.2022.899286
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plasma Membrane Sodium/Hydrogen Exchangers in Gastrointestinal Functions: Proliferation and Differentiation, Fluid/Electrolyte Transport and Barrier Integrity

Abstract: The five plasma membrane Na+/H+ exchanger (NHE) isoforms in the gastrointestinal tract are characterized by distinct cellular localization, tissue distribution, inhibitor sensitivities, and physiological regulation. NHE1 (Slc9a1) is ubiquitously expressed along the gastrointestinal tract in the basolateral membrane of enterocytes, but so far, an exclusive role for NHE1 in enterocyte physiology has remained elusive. NHE2 (Slc9a2) and NHE8 (Slc9a8) are apically expressed isoforms with ubiquitous distribution alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 365 publications
(582 reference statements)
0
10
0
Order By: Relevance
“…31 Currently, research has found that SLC9A2 is not only expressed in gastrointestinal epithelial cells, but also expressed in kidney, endometrium and chondrocytes. 30 A few of studies have shown that SLC9A2 can be used as a potential we attested for the first time that SLC9A2 could curb the proliferation and invasion of OS cells. Therefore, it is necessary to investigate the mechanism of SLC9A2 in OS.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…31 Currently, research has found that SLC9A2 is not only expressed in gastrointestinal epithelial cells, but also expressed in kidney, endometrium and chondrocytes. 30 A few of studies have shown that SLC9A2 can be used as a potential we attested for the first time that SLC9A2 could curb the proliferation and invasion of OS cells. Therefore, it is necessary to investigate the mechanism of SLC9A2 in OS.…”
Section: Discussionmentioning
confidence: 91%
“…The encoded protein is localized to the apical membrane and is easily degraded by lysosomes, resulting in a short half-life. 30 SLC9A2 is involved in sodium ion transport by exchanging intracellular hydrogen ions into external sodium ions, and helps in the regulation of cell pH and volume to eliminate acids produced by active metabolism or against adverse environmental conditions. 31 Currently, research has found that SLC9A2 is not only expressed in gastrointestinal epithelial cells, but also expressed in kidney, endometrium and chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, NHE2 is expressed in the crypts in mice or on the whole surface of the villus or upper half of the colonic crypt in rabbits. 51 , 52 Yet, no published report shows the expression of NHE2 in the human intestine. At the mRNA level, however, NHE2 is expressed throughout the vertical axis of the crypt in the human colon.…”
Section: Discussionmentioning
confidence: 99%